The Transmission of Liquidity Shocks : The Role of Internal Capital Markets and Bank Funding Strategies - Karam, Philippe (IMF Working Papers; Working Paper ;, 2014)
We analyze the transmission of bank-specific liquidity shocks triggered by a credit rating downgrade through the lending channel. Using bank-level data for US Bank Holding Companies, we find that a credit rating downgrade is associated with an immediate and persistent decline in access to non-core deposits and wholesale funding, especially during the global financial crisis. This translates into a reduction in lending to households and non-financial corporates at home and abroad. The effect on domestic lending, however, is mitigated when banks (i) hold a larger buffer of liquid assets, (ii) diversify away from rating-sensitive sources of funding, and (iii) activate internal liquidity support measures. Foreign lending is significantly reduced during a crisis at home only for subsidiaries with weak funding self-sufficiency.